Apparatus, system, and method for open frames for sport decks - FRANCOM JUSTIN; FRANCOM LARRY (2013)
A sport deck is formed with at least one pattern of tow fibers forming a platform for supporting a weight of a user when riding on a sport deck. The pattern of tow fibers form at least one through opening and at least one intersection of the tow fibers in which at least some of the tow fibers overlie others of the tow fibers. The intersections may be formed with tow fibers of a plurality of materials overlying each other to form layers having a plurality of respective characteristics. The platform may comprise a plurality of patterns of tow fibers. The intersection may be selectively located to strengthen the deck. The tow fibers may form a frame with a skin at least partially covering the frame of tow fibers.